KAJIAN PENGGUNAAN KATALISATOR ASAM SULFAT DAN LAMA PEMASAKAN PADA PROSES PRODUKSI PULP ACETOSOLVE DARI AMPAS TEBU DAN BAMBU BETUNG - Ahmad Sapta Zuidar; Sri Hidayati; Jamhuri - (Jurnal Teknologi & Industri Hasil Pertanian, 2013)
Pulp production requires raw materials that have high cellulose and hemicellulose content.  Alternative materials that can be used in the production of pulp are sugarcane bagasse and betung bamboo.  The production process of pulp used in this study was the acetosolve.  Acetosolve process was pulp production processes that use acetic acid as an organic solvent.  The objectives of this research were to find out the H2SO4 concentration and duration of pulp cooking to produce acetosolve pulp that have the highest yield, cellulose, hemicellulose, and lignin.  The research was arranged within a Complete Randomized Block Design in factorial with three replications.  The first factor was five levels of the concentration catalyst  (H2SO4): (K1) 0,125%, (K2) 0,25%, (K3) 0,5%, (K4) 1%, and (K5) 2%; and the second factor was two levels of the cooking duration:  (L1) 2 hours and (L2) 4 hours.  Data were analyzed using ANOVA and further tested using LSD at 5% level ofsignificance.  The results showed that the best pulping condition was found at 0,5% H2SO4 and two hours cooking duration.  The highest yield of pulp acetosolve was 81,42%, and its characteristics were:  83,57% of cellulose, 5,43% of hemicellulose, and 9,52% of lignin. Keywords: acetosolve pulp,  betung bamboo, sugarcane bagasse.